A statistical process control study on Atlanta Industries, Inc. - Lagunay, Novis; Papio, Marivic; Venida, Venice A. (Diliman, Quezon City College of Engineering, 2001)
Atlanta Industries,Inc. is a manufacturing company that employs the extrusion process in the production of pipes and piping systems.Currently,rejection resets have caused profit losses due to the variability of the wall thickness,failure of the heat reversion test,and the appearance of a wavy surface of Blue In-House Potable Water Pipes.A statistical Process Control was applied to the different areas of concern mentioned.For every area of concern,a process was analyzed.Control charts for wall thickness were out of control,and process capability ranged from low of 0.675(shit 1,minimum wall thickness)to a high of 2.15(shift 1 maximum wall thickness).Control charts for Heat Reversion Test were in control,with a process capability of 0.854,which is adequate but unacceptable.Control charts for wavy surface were in control.However,process is incapable.A verification matrix was used in solving the problem.To address the verified causes of the problem,recommendations were (1)the purchase of speedometer for constant of actual speed (2)constant monitoring of actual measurements of temperature and vacuum pressure (3)regular maintenance of the machine.It also recommended to implement Statistical Process Control, and to reevaluate the company's Systems and Procedure.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Atlanta Industries Incorporated; Manufacturing industries; Quality control